Principal professional identity: giving voice to children in a vulnerable Spanish context. - Lucena Rodríguez, Carmen; Cruz-González, Cristina; Domingo Segovia, Jesús (SAGE, 2021)
This case study investigated the strategies used by a school principal who successfully leads an educational centre in a vulnerable context. This article aims to explore how a school in a vulnerable context can be strengthened by the actions implemented by the principal and his leadership based on social and pedagogical commitment. Initially, the key aspects identified by the school community in the principal’s identity were analysed, and subsequently compared with their own perception to understand their professional development and leadership practices. The findings identify three main strategies that have been implemented to improve the school climate: (a) building relationships and involving the community in educational change; (b) enhancing cooperative work and the joint vision of the school–professional learning communities; and (c) give children a voice, respect children and fight for equal opportunities. Comprehensive keys to professional practice are drawn from these findings.
https://v2.sherpa.ac.uk/id/publication/9123
Keywords: Liderazgo en la enseñanza; Identity; Educational leadership; Principals; Student success; Social justice